Molecular Regionalization of the Diencephalon - Martinez-Ferre, Almudena; Martinez, Salvador (Frontiers in Neuroscience, 2012)
The anatomic complexity of the diencephalon depends on precise molecular and cellular regulative mechanisms orchestrated by regional morphogenetic organizers at the neural tube stage. In the diencephalon, like in other neural tube regions, dorsal and ventral signals codify positional information to specify ventro-dorsal regionalization. Retinoic acid, Fgf8, BMPs, and Wnts signals are the molecular factors acting upon the diencephalic epithelium to specify dorsal structures, while Shh is the main ventralizing signal. A central diencephalic organizer, the zona limitans intrathalamica (ZLI), appears after neurulation in the central diencephalic alar plate, establishing additional antero-posterior positional information inside diencephalic alar plate. Based on Shh expression, the ZLI acts as a morphogenetic center, which cooperates with other signals in thalamic specification and pattering in the alar plate of diencephalon. Indeed, Shh is expressed first in the basal plate extending dorsally through the ZLI epithelium as the development proceeds. Despite the importance of ZLI in diencephalic morphogenesis the mechanisms that regulate its development remain incompletely understood. Actually, controversial interpretations in different experimental models have been proposed. That is, experimental results have suggested that (i) the juxtaposition of the molecularly heterogeneous neuroepithelial areas, (ii) cell reorganization in the epithelium, and/or (iii) planar and vertical inductions in the neural epithelium, are required for ZLI specification and development. We will review some experimental data to approach the study of the molecular regulation of diencephalic regionalization, with special interest in the cellular mechanisms underlying planar inductions.